Lysis of lysis-inhibited bacteriophage T4-infected cells. - Abedon, S T (1992)
T4 bacteriophage (phage)-infected cells show a marked increase in latent-period length, called lysis inhibition, upon adsorption of additional T4 phages (secondary adsorption). Lysis inhibition is a complex phenotype requiring the activity of at least six T4 genes. Two basic mysteries surround our understanding of the expression of lysis inhibition: (i) the mechanism of initiation (i.e., how secondary adsorption leads to the expression of lysis inhibition) and (ii) the mechanism of lysis (i.e., how this signal not to lyse is reversed). This study first covers the basic biology of the expression of lysis inhibition and lysis of T4-infected cells at high culture densities. Then evidence is presented which implies that, as with the initiation of lysis inhibition, sudden, lysis-associated clearing of these cultures is likely caused by T4 secondary adsorption. For example, such clearing is often observed for lysis-inhibited T4-infected cells grown in batch culture during T4 stock preparation. The significance of this secondary adsorption-induced lysis to wild T4 populations is discussed. The study concludes with a logical argument suggesting that the lytic nature of the T4 phage particle evolved as a novel mechanism of phage-induced lysis.